Sources of Distress for Residents With Chronic Critical Illness and Ventilator Dependence in Long-Term Care. (February 2021) - Howard, A. Fuchsia; Crowe, Sarah; Choroszewski, Laura; Kovatch, Joe; J. Haynes, Adrianne; Ford, Joan; Beck, Scott; Haljan, Gregory J.
Limited understanding of the psychological challenges experienced by individuals with chronic critical illness hampers efforts to deliver quality care. We used an interpretive description approach to explore sources of distress for individuals with chronic critical illness in residential care, wherein we interviewed six residents, 11 family members, and 21 staff. Rather than discuss physical symptoms, sources of distress for residents were connected to feeling as though they were a patient receiving medical care as opposed to an individual living in their home. The tension between medical care and the unmet need for a sense of home was related to care beyond the physical being overlooked, being dependent on others but feeling neglected, frustration with limited choice and participation in decision making, and feeling sad and alone. Efforts to refine health care for individuals with chronic critical illness must foster a sense of home while ensuring individuals feel safe and supported to make decisions.